Changes in the phenotype of monocytes/macrophages and expression of cytokine mRNA in peripheral blood and synovial fluid of patients with rheumatoid arthritis. - Highton, J (1995)
Data from a previous study suggested that peripheral blood monocytes in patients with rheumatoid arthritis (RA) may be activated. Therefore, in this study we sought further evidence of 'presynovial' activation of monocytes. Our results show that phenotypic changes are demonstrable in peripheral blood monocytes in patients with RA, including increased expression of CR3 (CD11b/CD18) and FcRI (CD64). However, changes are most extensive in synovial monocytes/macrophages and especially for HLA-DR and intercellular adhesion molecule-1 (ICAM-1) (CD54). We conclude that monocyte/macrophage activation is most evident within the joint, and that 'presynovial' changes occur but are of limited extent.